1999
DOI: 10.2307/1061283
|View full text |Cite
|
Sign up to set email alerts
|

Persistence in International Inflation Rates

Abstract: We are grateful to Pedro de Lima and Uwe Hassler for providing their software and assistance in its modification. We acknowledge the helpful comments of two anonymous reviewers and a coeditor of this journal. The standard disclaimer applies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 30 publications
(5 reference statements)
4
44
0
Order By: Relevance
“…Similar evidence of strong long memory in the in ‡ation rate of the United States, United Kingdom, Germany, France, and Italy is also provided by Hassler and Wolters (1995). Baum, Barkoulas, and Caglayan (1999) found signi…cant evidence of long memory in the in ‡ation rates for the industrial as well as the developing countries. Baillie et al (2002) explore the long memory property in the …rst and second conditional moments of in ‡ation rates simultaneously.…”
Section: Introductionsupporting
confidence: 69%
“…Similar evidence of strong long memory in the in ‡ation rate of the United States, United Kingdom, Germany, France, and Italy is also provided by Hassler and Wolters (1995). Baum, Barkoulas, and Caglayan (1999) found signi…cant evidence of long memory in the in ‡ation rates for the industrial as well as the developing countries. Baillie et al (2002) explore the long memory property in the …rst and second conditional moments of in ‡ation rates simultaneously.…”
Section: Introductionsupporting
confidence: 69%
“…Malliaropoulos (2000) [14] and Baum et al (1999) [19] showed that USA nominal interest and inflation rates can be better represented using broken trend stationary models. This finding is very important in the sense that, at least for the USA data, it casts doubts on the adequacy of the co-integration approach to test for the Fisher effect.…”
Section: Fisher Effect With Non-integrated Variablesmentioning
confidence: 99%
“…Similarly, some other authors suggest the possibility that these variables may follow a long-memory process. We can cite the papers of Baum et al (1999) [19], Phillips and Perron (1998) [20], Tsay (2000) [21], Sun and Phillips (2004) [22], Gil-Alaña (2004) [23] and Gil-Alaña and Moreno (2012) [24], in the case of the nominal interest rate, and Hassler and Wolters (1995) [25] and Bos et al (1999) [26] with respect to the inflation rate. In light of this, the use of the unit root/co-integration approach is now open to debate.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Baum, Barkoulas and Caglayan (1999) estimated fractional ARIMA (ARFIMA) models for real exchange rates in the post-Bretton Woods era and found almost no evidence to support long run PPP. Additional studies on exchange rate dynamics using fractional integration are those by Crato and Ray (2000), Wang (2004), Dufrenot et al (2006Dufrenot et al ( , 2008 and Aloy et al (2011) among others.…”
Section: Introductionmentioning
confidence: 99%